Analysis of Laboratory Utilization in Supporting Physics Learning: A Case Study at Metro Public High School 5 - Riswanto Riswanto; Wari Prastiti; Friska Octavia Rosa; Dian Utama Hartanto Setya Putra; Febi Afifah; anggun saputri (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
This study aims to provide a more in-depth analysis of laboratory utilization at SMAN 5 Metro. The research employed a qualitative approach. The object of this study was SMAN 5 Metro, with class XI students and physics teachers as the research subjects. Data were collected through three techniques: observation, interviews, and questionnaires. The data analysis was conducted both during and after the data collection process. The analysis technique used was data triangulation, which involved comparing findings from the three data sources (observations, interviews, and questionnaires). Based on the results of the data analysis, it can be concluded that practicum activities at SMA Negeri 5 Metro are still conducted in the classroom, with teachers bringing practicum tools into the classroom to demonstrate and carry out experiments. In addition, practicum implementation has not been optimal due to improper laboratory utilization, the use of laboratory spaces that do not align with their intended functions, and the absence of laboratory assistants or technicians. These personnel are essential for managing laboratory administration, including maintaining inventory records of tools and materials, handling equipment loans, and organizing tools and materials according to their types and characteristics.